The metabolic and physiologic impairments underlying long COVID associated exercise intolerance - Brooks P. Leitner; Phillip Joseph; Andres Figueroa Quast; Maria Alejandra Ramirez; Paul M. Heerdt; Jose G. Villalobos; Inderjit Singh (Pulmonary Circulation)
Abstract Data from invasive CPET (iCPET) revealed long COVID patients have impaired systemic oxygen extraction (EO2), suggesting impaired mitochondrial ATP production. However, it remains uncertain whether the initial severity of SARS‐CoV‐2 infection has implications on EO2 and exercise capacity (VO2) nor has there been assessment of anerobic ATP generation in long COVID patients. iCPET was performed on 47 long COVID patients (i.e., full cohort; n = 8 with severe SARS‐CoV‐2 infection). In a subset of patients (i.e., metabolomic cohort; n = 26) metabolomics on venous and arterial blood samples during iCPET was performed. In the full cohort, long COVID patients exhibited reduced peak EO2 with reduced peak VO2 (90 ± 17% predicted) relative to cardiac output (118 ± 23% predicted). Peak VO2 [88% predicted (IQR 81% ‐ 108%) vs. 70% predicted (IQR 64% ‐ 89%); p = 0.02] and EO2 [0.59(IQR 0.53–0.62) vs. 0.53(IQR 0.50–0.48); p = 0.01) were lower in severe versus mild infection. In the metabolomic cohort, 12 metabolites were significantly consumed, and 41 metabolites were significantly released (p‐values < 0.05). Quantitative metabolomics demonstrated significant increases in inosine and succinate arteriovenous gradients during exercise. Peak VO2 was significantly correlated with peak venous succinate (r = 0.68; p = 0.0008) and peak venous lactate (r = 0.49; p = 0.0004). Peak EO2 and consequently peak VO2 impact long COVID patients in a severity dependent manner. Exercise intolerance associated with long COVID is defined by impaired aerobic and anaerobic energy production. Peak venous succinate may serve as a potential biomarker in long COVID.